How to Measure Water in Oil? - Jamshidbek Ulugbek ugli Shamuratov (Zien Journals, 2021)
Determining the amount of water in the oil and controlling it is one of the important problems. There are several ways to determine the amount of water (moisture content of oil) in oil in an industry or laboratory around the world. The article describes these methods of determining oil moisture, their advantages and disadvantages. Measuring and controlling the moisture content of oil will lead to an improvement in quality in industry and consumption of petroleum products. The main goals of modern scientists and instrument manufacturers are the creation and automation of modern oil moisture measuring instruments.
Keywords: water; moisture; volume of humidity; temperature